Optimization of β-galactosidase production using Kluyveromyces lactis NRRL Y-8279 by response surface methodology - Dagbagli, Seval; Goksungur, Yekta (Electronic Journal of Biotechnology, 2008)
This paper investigates the production and optimization of β-galactosidase enzyme using synthetic medium by Kluyveromyces lactis NRRL Y-8279 in shake flask cultures. Among the different cell disintegration methods used, the highest specific activity was obtained when the cells were permeabilized using isoamyl alcohol. Response surface methodology was used to investigate the effects of four fermentation parameters (agitation speed, pH, initial substrate concentration and incubation time) on β-galactosidase enzyme production. Results of the statistical analysis showed that the fit of the model was good in all cases. Maximum specific enzyme activity of 4218.4 U g-1 was obtained at the optimum levels of process variables (pH 7.35, agitation speed 179.2 rpm, initial sugar concentration 24.9 g l-1 and incubation time 50.9 hrs). The response surface methodology was found to be useful in optimizing and determining the interactions among process variables in β-galactosidase enzyme production.